2022
DOI: 10.3390/diagnostics12112889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Imaging and 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Diagnostic Accuracy of Staging in Patients with Intrahepatic Cholangiocarcinoma

Abstract: We aimed to examine the accuracy of tumor staging of intrahepatic cholangiocarcinoma (ICC) by using 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET-CT). From January 2001 to December 2021, 202 patients underwent PET-CT, CT, and MRI for the initial staging of ICC in two institutions. Among them, 102 patients had undergone surgical treatment. Ninety patients who had a histopathological diagnosis of ICC were retrospectively reviewed. The sensitivity and specificity of 18F-FDG … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The theme of recurrence was also explored through MRI. The results achieved were comparable to the ones achieved by CT images analysis [ 192 , 193 , 194 , 195 , 196 ]. In the study by Xu et al, to predict early and late recurrence, features were extracted from the intratumoral and peritumoral area.…”
Section: Resultssupporting
confidence: 77%
“…The theme of recurrence was also explored through MRI. The results achieved were comparable to the ones achieved by CT images analysis [ 192 , 193 , 194 , 195 , 196 ]. In the study by Xu et al, to predict early and late recurrence, features were extracted from the intratumoral and peritumoral area.…”
Section: Resultssupporting
confidence: 77%
“…However, previous studies reported that the sensitivity and specificity of CT/MRI varied from 35.0% to 78.2% [ 30 , 31 ], which strongly calls for more precise detection methods. Recent studies reported that 18-F fluorodeoxyglucose (FDG) PET-CT [ 32 , 33 ] showed significantly higher sensitivity, specificity and accuracy than conventional CT/MRI in diagnosing regional LNM, which may facilitate tumor staging in ICC. Besides, artificial intelligence-based radiomics [ 34 , 35 ] also performed well in metastatic nodal discrimination, enabling accurate N staging of ICC and patient risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al reported that 18 F-FDG PET/CT is more effective than CT/MRI in identifying lymph node and distant metastases ( 10 ). They first identified several points of interest for 18 F-FDG PET/CT in the initial staging of iCCA: the detection ability of 18 F-FDG PET has a clinically important impact on tumor-node-metastasis (TNM) staging and treatment planning for iCCA ( 11 ), and the ability of 18 F-FDG PET/CT to detect distant metastases in the early stages of iCCA is of great importance in the staging of iCCA. Detected distant metastases may be missed by CT/MRI, but can be accurately identified by 18 F-FDG PET/CT.…”
mentioning
confidence: 99%
“…Some studies have reported that lymph node status is highly related to the prognosis of iCCA ( 11 , 12 ). Lin et al also reported that treatment allocation was significantly different, with 83.6% of patients treated curatively with conventional imaging and 90.5% of patients treated with both PET/CT and conventional imaging (P=0.033), establishing the influence of PET/CT on clinical treatment strategy (P=0.033), demonstrating the impact of PET/CT on clinical treatment strategies.…”
mentioning
confidence: 99%